The Genetic Algorithm: A study survey - mohsin, rewayda razaq (Iraqi Journal of Science, 2022)
Genetic Algorithms (GA) is a based population approach. It belongs to a metaheuristic procedure that uses population characteristics to guide the search. It maintains and improves multiple solutions which may produce a high-quality solution to an optimization problem. This study presents a comprehensive survey of the GA. We provide and discuss genetic algorithms for new researchers. We illustrate which components build up the GAs and view the main results on complexity time.